Leveraging the Rapid Retreat of the Amundsen Gulf Ice Stream 13, 000 Years Ago to Reveal Insight Into North American Deglaciation. Issue 21 (11th November 2019) - Pico, T.; Robel, A.; Powell, E.; Mix, A. C.; Mitrovica, J. X.
Abstract: We examine the influence of different deglacial histories of the North American ice saddle, which connected the Cordilleran ice sheet and western Laurentide ice sheet, on the stability of the fast‐flowing Amundsen Gulf Ice Stream, located in the northwestern Laurentide ice sheet. We use a simplified marine‐terminating ice stream model to simulate grounding line retreat and compare our predictions to geologic evidence for the rapid collapse of the Amundsen Gulf Ice Stream at 13 ka. We show that observations of ice stream retreat can be used to distinguish between past ice unloading histories, and that the rapid retreat of the Amundsen Gulf Ice Stream near 13 ka is most dynamically consistent with substantial deglaciation of the North American ice saddle from 13 to 11.5 ka, during the Younger Dryas cooling episode. These results suggest that short‐lived changes in ice stream behavior may be used to reveal larger‐scale and longer‐duration ice sheet dynamics. Key Points: Ice streams are sensitive to history of deglaciation We use ice stream collapse to differentiate between proposed deglacial ice histories